Impact of Door-to-Needle Time on Outcomes in Acute Ischemic Stroke Treated with Intravenous Thrombolysis at Thrombectomy-Capable Centers: A Systematic Review - Grace Septi Yudanthi Kerihi; Werenfridus Rainoldy Resdiana Wangi; Sri Suryati Ningsih Putri Kusumo (Jurnal KESANS : Kesehatan dan Sains, 2026)
Introduction: Acute ischemic stroke (AIS) is a leading cause of disability and mortality worldwide, with intravenous thrombolysis (IVT) serving as the cornerstone of reperfusion therapy. Door-to-needle time (DTN) represents a key modifiable determinant of IVT effectiveness, yet its clinical impact in thrombectomy-capable settings remains incompletely defined Objective: To evaluate the association between DTN and clinical outcomes in AIS patients undergoing IVT in thrombectomy-capable centers. Methods: A systematic review was conducted following PRISMA 2020 guidelines, with searches performed across PubMed, Cochrane Library, and ScienceDirect. Adult AIS patients treated with IVT, with or without thrombectomy, were included. Outcomes of interest were functional independence, mortality, and symptomatic intracerebral hemorrhage Results and Discussion: Four studies were included. Shorter DTN, particularly under 60 minutes, was consistently associated with reduced mortality and superior neurological recovery in a dose-dependent manner. No significant association was identified between shorter DTN and increased hemorrhagic risk. The findings support the time-dependent effectiveness of intravenous thrombolysis, even in the era of endovascular thrombectomy. Early thrombolysis may enhance reperfusion and improve downstream outcomes. Despite heterogeneity across studies, the overall direction of evidence was consistent. Conclusion: Reducing door-to-needle time remains a critical priority in acute stroke management, including in thrombectomy-capable centers, and should be emphasized in workflow optimization strategies